MAMMALS FROM CHIAPAS - VILLA RAMIREZ, BERNARDO (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1964)
A series of Ambystoma larvae from Cuyamaloya is descr in detail and typical specimens figured Adult characters not being evident, the specimens are not assigned to spp, but are compared with larvae of A tigrinum velascoi and A lacustris
ANS INST BIOL
Keywords: MAMMALS, CHIAPAS; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL